MAKTABGACHA TA’LIM TIZIMIDA BOSHQARUV MADANIYATINI RIVOJLANTIRISHNING ILMIY-PEDAGOGIK ASOSLARI (Conferencea, 2022)
Development of scientific and methodological training of leaders in the management of continuing education, especially preschool education, in the process of socio-economic, spiritual and educational changes in the Republic of Uzbekistan, developing market economy relations, development in science, technology and information globalization the issue is a pressing issue. Taking into account the social order of the preschool education system, the existing shortcomings in the scientific and methodological training of managers can be overcome by retraining and improving their skills, as well as the organization of independent work on them. The need to equip them with modern pedagogical theories, educational technologies is one of the great tasks facing the industry.